Analisis Faktor Pemilihan Jajanan, Kontribusi Gizi dan Status Gizi Siswa Sekolah Dasar - Anggiruling, Dwikani Oklita; Ekayanti, Ikeu; Khomsan, Ali (Media Kesehatan Masyarakat Indonesia, 2019)
Fulfillment children’s nutritional needs is important to support growth and development. The dietary habit of school-age children which tends to prefer snacks at school rather than eating at homewill affect the nutritional status of children. The purpose of this study was to analyze determinant factors of snacks choice, relationship between snacks choice with frequency of snacks, and relationship of nutrition contribution of snacks with nutritional status of children. This study was a cross-sectional study funded by the Neys-van Hoogstraten Foundation, the Netherlands and was conducted at three primary schools namely SDN Kedokan, SDN Pajajaran and SDN Cibogo in Cisauk Sub-District, Tangerang Regency with total subjects of this study were 109 students. Factor-analysisand Rank Spearman relationship tests were used to analyze data. There are five main factors that determine thesnacks choice, namely familiarity factor, characteristics of snacks, environmental and social, nutritional content and variation, and health. Health factors and snack characteristics had significant relationships with frequency of snacks (p<0.05). The contribution of energy, protein, fat and carbohydrate had significant relationships with the nutritional status of children (p<0.05). The study resultshows that snack choice played an important role in snacking habits and nutrition contribution of snacks had an impact on nutritional status of children, therefore availability of snacks at school should consider the children’s snack choice and nutritioncontribution of snacks.